Eco-literate societies: the interplay of education, environmental policy stringency, and digital innovation in BRICS nations - Zhang, Xiaojuan; Xiao, Lingshan (Frontiers in Environmental Science, 2025)
As emerging global economic powers, BRICS nations face a critical challenge in balancing rapid development with environmental sustainability. While industrial expansion, digital transformation, and urbanization have accelerated economic growth, these trends have also intensified ecological pressures, necessitating comprehensive policy solutions. Recognizing this urgency, the present study examines the determinants of environmental sustainability in BRICS nations from 1990 to 2023, focusing on economic growth (E.G.,), urbanization (URB), education (EDU), digital innovation (DI), and environmental policy stringency (EPS). By addressing the complex interactions among these variables, the study aims to provide empirical insights into how socioeconomic and technological advancements shape environmental outcomes. To achieve this, the study employs the Method of Moments Quantile Regression (MMQR) to capture heterogeneous effects across different sustainability levels, Feasible Generalized Least Squares (FGLS) for robustness validation, and Granger causality analysis to establish directional relationships. The findings reveal a nonlinear role of education, where in the linear model, EDU exacerbates environmental degradation due to its early association with industrial expansion. However, in the nonlinear model incorporating EDU2, education exhibits an inverted U-shaped effect, initially straining the environment but later fostering sustainability as higher attainment levels promote ecological awareness and technological innovation. Urbanization consistently enhances sustainability across models, while digital innovation imposes environmental burdens, highlighting the need for green technological policies. Economic growth presents mixed effects, suggesting that regulatory interventions are required to steer economic expansion toward sustainable pathways. The study’s novelty lies in its empirical approach, uncovering threshold effects of education and asymmetries in digital innovation’s environmental impact, providing deeper insights into sustainability dynamics within emerging economies. The policy implications are profound—governments must integrate sustainability into education reforms, urban development strategies, and digital regulatory frameworks to ensure long-term ecological resilience. By aligning sustainability policies with SDG commitments and COP climate agreements, BRICS nations can effectively transition toward a green economic model, balancing development with environmental stewardship.